Case Report: Colchicine Toxicokinetic Analysis in a Poisoned Child Requiring Extracorporeal Life Support - Pérez Marín, Maria; Prod'hom, Sylvain; de Villiers, Suzanne Francesca; Ferry, Thomas; Amiet, Vivianne; Natterer, Julia; Perez, Maria-Helena; Buclin, Thierry; Chtioui, Haithem; Longchamp, David (Frontiers in Pediatrics, 2021)
Colchicine poisoning is associated with a poor prognosis, especially when leading to shock and multi-organ failure, and management is limited to supportive care, including multiple-dose activated charcoal. At therapeutic concentrations, colchicine elimination occurs mainly through hepatic metabolism and involves an enterohepatic circulation, with a small contribution of renal elimination (10–30%). Colchicine toxicokinetics is however rarely described, especially in children. We present the case of a 4-year-old patient who survived a severe iatrogenic colchicine intoxication with a dose of 0.5 mg/kg. She developed multi-organ failure and shock, but recovered after receiving aggressive resuscitation, including extracorporeal life support. Close monitoring of colchicine blood levels showed a plateau for 6 days, indicating impeded elimination resulting from liver failure. We observed no significant clearance from renal replacement therapy, nor activated charcoal, during this period. Extracorporeal life support may play a supportive role in the management of severe colchicine poisoning. However, extracorporeal techniques do not seem to improve colchicine elimination.